PENGARUH MOTIVASI MENGHINDARI RIBA DAN PENGETAHUAN PRODUK KOPERASI SYARIAH TERHADAP KEPUTUSAN MENJADI NASABAH DI KOPERASI SIMPAN PINJAM PEMBIAYAAN SYARIAH (KSPPS) NUR HAYYU AMBARA NTB - Danang Prio Utomo; Huzain Jailani; Regita Ayu Cahyati (UIN Mataram, 2021)
This study aims to analyze partially and simultaneously the effect of the motivation to avoid usury and knowledge of sharia cooperative products on the decision to become a customer in the Sharia Savings and Loans Payment Cooperative Nur Hayyu Ambara NTB. This study uses quantitative methods. The sampling technique is Non Probability Sampling with Incidental Sampling sampling technique. The number of respondents in this study were 60 respondents. Data collection using a questionnaire and then processed using SPSS 16. Data analysis techniques using validity test, reliability test, classical assumption test, multiple linear regression test, partial test (t test), simultaneous test (f test), and coefficient of determination test (R2). The results of this study indicate that partially the motivation to avoid usury has no significant effect on the decision to become a customer of the Sharia Savings and Loans Payment Cooperative Nur Hayyu Ambara, The results of the coefficient of determination (R2) show that the influence of motivation to avoid usury and product knowledge on the decision to become a customer of the Sharia Savings and Loans Payment Cooperative Nur Hayyu Ambara NTB is 31.1% while the remaining 69.9% is influenced by factors outside the model